What a delayed political succession means for Singapore - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2021)
In a commentary, SMU Associate Professor of Law Eugene Tan discussed the implications of what a delayed political succession might mean for Singapore. He also explained how the search for Deputy Prime Minister Heng Swee Keat's successor presents a new test for Singapore’s leaders, and highlighted the key focus for leadership renewal amid the pandemic.